2007
DOI: 10.1111/j.1600-0536.2007.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and correlation between stinging responses to lactic acid and bioengineering parameters

Abstract: In evaluating the safety of a novel cosmetic product or a new chemical, it is important to assess susceptible population. One group of subjects is known to stingers who are more likely to experience sensory effects such as stinging and burning after contacting with cosmetics. The purpose of the study is to measure skin biophysical parameters noninvasively in stingers and non-stingers and to see their correlations with stinging responses. 298 women were evaluated by modified lactic acid stinging test with 5% la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
65
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 14 publications
6
65
0
Order By: Relevance
“…A lower CAP at baseline predicted earlier onset of stinging and a weak correlation (Spearman's test: r = 0.307, p = 0.03), with a higher clinical stinging score identified [39]. On the other hand, other studies found no difference in CAP between stingers and nonstingers [40,50,51] or between subjects with sensitive and nonsensitive skin [20,48], either challenged or unchallenged [20,48,51]. The lower CAP is consistent with findings of a clinically dryer skin [15] and a lower facial ceramide content of the stratum corneum found in subjects with sensitive skin (p = 0.037) [38].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A lower CAP at baseline predicted earlier onset of stinging and a weak correlation (Spearman's test: r = 0.307, p = 0.03), with a higher clinical stinging score identified [39]. On the other hand, other studies found no difference in CAP between stingers and nonstingers [40,50,51] or between subjects with sensitive and nonsensitive skin [20,48], either challenged or unchallenged [20,48,51]. The lower CAP is consistent with findings of a clinically dryer skin [15] and a lower facial ceramide content of the stratum corneum found in subjects with sensitive skin (p = 0.037) [38].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 10 studies presented data on hydration of the stratum corneum (measured through capacitance, CAP) in sensitive skin (table 1). A significantly lower CAP at facial areas in subjects with sensitive skin [37] and in stingers [40] and a nonsignificantly lower CAP at facial areas in subjects with sensitive skin were found [41]. Challenging the skin with octane or cumene, however, resulted in a significantly lower CAP in stingers compared to nonstingers [51].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations